Expert Study of the Execution of the Terms of an Investment Life Insurance Contract - O. A. Abelev; M. M. Vinogradova; M. G. Nersesyan (Теория и практика судебной экспертизы, 2021)
A significant decrease in bank deposits’ profitability forces citizens to look for more profitable investment options, including purchasing various financial products. One such product is an investment life insurance contract. However, investors’ expectations are not always fully met since dealing with financial instruments, such as options, requires a certain of financial literacy, understanding of the futures stock market’s organization and functioning. Arising disputes are often resolved in court. To obtain answers to economical questions, a forensic examination is appointed and carried out.Forensic analysis on this topic has some features that are discussed in the article. The paper gives a list of objects for expert research and their brief characteristics. The main sources of reference information on quotations of financial instruments are provided. Some concepts and economic categories related to the stock market and derivatives are considered. The Russian and English terms used by the experts during the study are presented and explained.Using an example from expert practice, the authors explain the logic of the analysis of an option contract and show the sequence of actions that makes it possible to calculate the investment income amount. The article justifies the conditions that restrict the experts when carrying out calculations and should be taken into account when forming and studying the expert opinions.